Study the Electromechanical Strength Properties for Epoxy Dispersed Silica Powder Composite - Zaidan, Shihab A.; Mohammed, Amani Z. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Powder Silica (SiO2) was added to epoxy polymer with different weight percentages  (3.75,7.5,11.25 and 15 wt%) for particle size ï‚£ 63 Âµm. Hand lay-up method it is used to prepared (Epoxy-Silica) composite, and cutting appropriate specimens for testing. Electrical strength varies nonlinearly with specimens thickness, also decreasing with average time for the rise of voltage decreases due to electro thermal effects. Clearly, electrical strength decreases with the increase of the proportion of added silica. The hardness, tensile strength and young modulus increased with the added silica increases due to changing in material characteristics from ductility to brittle. Microscopic cracks and irregularity deformation were appeared within electrical breakdown area, especially for high silica additives. While, fusion, perforation and regularity of electrical breakdown area were appeared for specimens with low and without silica additives